2017
DOI: 10.23956/ijermt/v6n2/129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Person-Job Fit, Person-Organization Fit, Information Sharing and Empowerment on Organizational Commitment of Moroccan Banks Managers

Abstract: Abstractuman resources are considered to be the most important factor within the organization to gain a competitive advantage. Develop organizational commitment of human resources is imperative to stimulate a long-term relationship with them. The primary objective of this study, on one hand, is to explore the relationship between the person-job fit, person-organization fit, information sharing and empowerment and organizational commitment working managers in head offices of Moroccan banks, on the other hand, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Its implications can show the extent to which the employees desire to stick with their organization (Robbins & Judge, 2016). This significant relationship has been found in several studies (Alla & Rajaa, 2017;Margaretha & Wicaksana, 2020;Nuansa et al, 2018;Pattnaik et al, 2020;Soelton, Noermijati, et al, 2020;Widodo et al, 2020). Thus, this research hypothesizes that person-organization fit has a significant positive effect on organizational commitment.…”
Section: Conceptual Frameworksupporting
confidence: 68%
“…Its implications can show the extent to which the employees desire to stick with their organization (Robbins & Judge, 2016). This significant relationship has been found in several studies (Alla & Rajaa, 2017;Margaretha & Wicaksana, 2020;Nuansa et al, 2018;Pattnaik et al, 2020;Soelton, Noermijati, et al, 2020;Widodo et al, 2020). Thus, this research hypothesizes that person-organization fit has a significant positive effect on organizational commitment.…”
Section: Conceptual Frameworksupporting
confidence: 68%
“…Research conducted by Jawad (2013), Hussain (2017), Alla (2017) shows that job characteristic, person-job fit, and organizational commitment has positive and significant effects on employee performance. In contrast, Leng (2016) study showed that the variable of job characteristics, person-job fit, and organizational commitment did not have a significant effect on employee performance.…”
Section: Introductionmentioning
confidence: 99%